Vulvar Myiasis - M. R. L. Passos; A. V. V. Carvalho; A. L. Dutra; R. A. Goulart Filho; N. A. Barreto; R. S. Salles; C. C. C. Santos; A. S. Tibúrcio; A. C. S. Monteiro; R. R. Tavares (Hindawi Limited, 1998)
Myiasis is a parasitic infestation caused by larvae of several fly species. Diagnosis and treatment are simple. This infestation is, however, rarely seen in the vulvar area. We present a short review of the disease and the case of a 19-year-old pregnant girl with vulvar myiasis and concomitant syphilis, vaginal trichomoniasis and genital candidiasis. The patient was also positive for human immunodeficiency virus.